Does multidetector computed tomography unravel the hidden domains of conventional radiography in calcaneal fractures? - Javaid Iqbal; Moonisah Rafiq; Abid Hussain (International Journal of Research in Orthopaedics, 2023)
Background: The most often fractured bone among the tarsal bones is the calcaneum. The first assessment of the suspected calcaneum fracture is conventional radiography. The modern assessment of calcaneal fractures is mainly based on multidetector computed tomography, because of its three-dimensional nature and Volume rendering techniques. The objective of this study was to compare the diagnostic value of Multidetector CT with Conventional radiography in Calcaneal fractures taking operative data as reference standard. Methods: The patients suspected for calcaneal fracture were subjected to conventional radiography and computed tomographic imaging and results were compared in terms of Sensitivity, specificity, positive predictive value, negative predictive value and Diagnostic accuracy, taking operative/MRI findings as reference standard. Results: We included 68 cases in our study The Sensitivity, specificity and diagnostic accuracy were 92.6%, 33.33%, 82.3% and 98.3%, 71.4%, 95.5% for conventional radiography and MDCT respectively. Conclusions: We settled that MDCT is far ahead of the conventional radiography in complete depiction, diagnosis, characterization and treatment formulation for calcaneal fractures.